Effects of potassium humate and chemical fertilizers on growth, yield and quality of rice (Oryza sativa L.) - Kumar, Dileep; Singh, AP; Raha, P; Singh, CM (Bangladesh Journal of Botany, 2015)
A pot experiment was conducted in Kharif 2009 and 2010 to study the effect of potassium humate and chemical fertilizers on growth and yield attributes of rice (Oryza sativa L). Potassium humate was applied at the rate of 0, 5 and 10 mg/kg soil along with 100 and 75% recommended dose of fertilizers NPK (60, 30, 30 mg/kg) and 12.5 mg/kg zinc sulphate was also applied. Addition of 10 mg/kg PH along with 100% NPK fertilizers and 12.5 mg/kg zinc sulphate caused significant increase in plant height, number of tillers, panicle height, panicle length, test weight, straw yield and yield of rice as compared to 100 and 75% NPK alone. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21671 Bangladesh J. Bot. 43(2): 183-189, 2014 (September)